The Impact Of Listening Strategy Instruction On Iranian Senior Efl Students’ Listening Comprehension, Metacognitive Awareness In Listening, And Listening Strategy Use - Zareian, Gholamreza (2010)

(untitled)
Many descriptive and experimental studies have shown a positive relationship between success in language learning and variables such as metacognitive awareness and learning strategy use. However, few studies have been done on how to improve metacognitive awareness in listening, listening strategy use, and listening comprehension. In this study, an attempt was made to determine the impact of listening strategy instruction on Iranian senior EFL (English as a Foreign Language) students’ listening comprehension, metacognitive awareness in listening, and listening strategy use. The objectives of the study are (1) to examine the effectiveness of listening strategy instruction in making students efficient listeners, frequent users of listening strategies, and more metacognitively aware of their listening; (2) to investigate the interrelationships among listening comprehension level, listening strategy use, and metacognitive awareness in listening; and (3) to identify the listening strategies learners actually use when they encounter problems during real-time listening and the effectiveness of these strategies